2022
DOI: 10.37745/ejaafr.2013/vol10n112135
|View full text |Cite
|
Sign up to set email alerts
|

Markov Chain and Inventory Management of Manufacturing Companies in Nigeria

Abstract: The inability to adapt and accept the deployment of new technologies in solving inventory-related problems have been some of the challenges manufacturing companies face in Nigeria. Some studies have suggested that the use of the Markov chain is capable of improving inventory management, however, the capabilities and effectiveness of the Markov chain in enhancing inventory management in manufacturing companies remain quite unclear. This study reviewed the Markov chain and inventory management of manufacturing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Further, an empirical investigation by Jabbari et al (2013) found an inverse and statistically significant impact of net cash generated from operations on financial performance. On the contrary, Oyadonghan and Bingilar (2014) found out that operating cash flows have significant positive relationship with corporate performance.…”
Section: Regression Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…Further, an empirical investigation by Jabbari et al (2013) found an inverse and statistically significant impact of net cash generated from operations on financial performance. On the contrary, Oyadonghan and Bingilar (2014) found out that operating cash flows have significant positive relationship with corporate performance.…”
Section: Regression Analysismentioning
confidence: 88%
“…The result is supported with evidence by Kramer andJohnson (2009) andWilliams, et al, (2014) who also reported a positive and statistically significant impact of financing cash flows on profitability. Oyadonghan and Bingilar (2014) also revealed that financing cash flows have significant positive relationship with corporate performance.…”
Section: Regression Analysismentioning
confidence: 92%